El e-commerce como estrategia de comercialización en el bar-restaurant Macawa del cantón Logroño - Armijos Sarmiento, Junior Adrián (2024)
The present investigative study focused on E-commerce as a marketing strategy in the Macawa BarRestaurant in the Logroño canton; therefore, to obtain relevant information from the personnel who work in the business, a research instrument was applied, which was the survey questionnaire and also through the hypotheticodeductive method it was possible to found and support the hypothesis correctly. It was evident that they did not have a defined strategy. Therefore, e commerce can become a relevant tool to market and attract customers due to its convertibility and application, which do not require additional costs, making it perfect for a new venture or expansion in the market. It is essential to mention that traditional methods of promoting a product have less relevance for the consumer every day, so it is necessary to innovate using the new electronic commerce channels that are trending worldwide and are part of the daily life of the new generations. That is why different marketing strategies were carried out based on e-commerce, which is recommended to apply to strengthen the business's weaknesses.